Forecasting analysis of selected health- and economy-related indicators in South Eastern European and Balkan countries - Stepović, Miloš; Vekić, Berislav; Dragojević Simić, Viktorija; Vekić, Stefan; Rančić, Nemanja (Vojnosanitetski pregled, 2022)
Background/Aim. Health indicators provide comparable information relevant to defining health goals. The aim of this study was to perform a forecasting analysis of the selected indicators, which could help anticipate the future necessities in the health economy and prevent the problems that would predictively grow in the future. Methods. Health indicators are collected from publicly available databases of the World Health Organization and Eurostat. We used the quantitative forecasting technique, commonly used for historical data, to predict several years in the future concerning selected health- and economy-related indicators. Results. Total health expenditures as a percentage of gross domestic product (GDP) by 2025 will increase in most of the 17 surveyed countries. The percentage of direct household budget payments (out-of-pocket) for health services will decrease in half of the countries, while values of GDP expressed in US$ will increase significantly compared to the last surveyed year (2017), except in Greece. The infant mortality indicator shows that the numbers will decrease in each surveyed country, while the urban population percentage will rise almost in each country except Estonia. Life expectancy will increase in each surveyed country. Conclusion. Health- and economy-related indicators must be monitored over time, as they provide significant information concerning the relevant issues in the health care system. Moreover, they may indicate changes that should be made in order to accomplish progress in each individual country.
Keywords: balkan peninsula; europe, eastern; forecasting; health care costs; health care economics and organization; health care evaluation mechanisms; health care reform; statistics; health status indicators.